Is the new fınancıal center ıstanbul compatıble wıth the European Unıon fınancıal norms - Gökay, Erden Ziya (My University, 2016)
Dünyada hem ticaret hem de iş merkezi olarak önemli bir yeri olan Londra, New York,Hong Kong gibi uluslararası finans merkezleri dünyanın en gözde mali kurumlarının yerleşik hal aldığı ve dünyadaki tüm finansal ürünlerin en üst düzeyde kullanıldığı finansal yönetim birimlerine dönüşmüşlerdir. Bu durum; söz konusu finans merkezlerinde yer alan firmalar için coğrafi ve stratejik açıdan pek çok faktörün yanında ölçek ekonomilerinden de yararlanma avantajı yaratırken içinde bulundukları şehir ve ülke ekonomilerine de ciddi katkılar sağlamaktadır. Bu tezde Türkiye'nin en önemli projelerinden biri olarak 2009 yılında başlayan İstanbul Finans Merkezi (İFM) projesinde şu ana dek yapılan çalışmalarda gelinen son aşama değerlendirilmiş, eylem planları, Avrupa Birliği (AB), General Agreement on Tariffs and Trade (GATTs) anlaşması gibi ulusal ve uluslararası normlara uyum sorgulanmıştır. AB müzakerelerine başlangıç tarihi olan Ekim 2005 ile Aralık 2015 tarihleri arasında dünyanın gelişmiş ülke borsaları endekslerinin ne ölçüde eşbütünleşik olduğu ekonometrik açıdan test edilmiştir.Yukarıda sözü edilen dönemde BORSA ISTANBUL (BİST) borsa endeksinin ABD, HONG KONG, DUBAI, EUROSTOXX50, İNGİLTERE ve İSVİÇRE borsaları ile eşbütünleşik olmadığı sonucuna varılmıştır. Söz konusu ampirik bulgu, değişkenler arasında uzun dönemli bağlantı olmadığı anlamına gelmektedir. İFM olma yolunda yapılan çalışmalar incelendiğinde gelişmiş finans merkezleri sıralamasında İstanbul'un oldukça yol almış olmasına rağmen henüz istenilen seviyeye ulaşmadığı görülmüştür. Istanbul Finans Merkezi, General Agreement on Tariffs and Trade (GATTs), Türkiye - AB İlişkileri, Avrupa Birliği, Uluslararası Finans Merkezleri, Eş Bütünleşme Analizi

It has an important place in both trade and business center in the world , International financial centers such as London, New York, Hong Kong having an important place in terms of both trade and business center have turned into financial management units in which the most popular of the world have become resident and all financial products of the world are used at the highest level. While this situation poses advantages for the companies in the said financial centers to benefit from scale economies as well as many factors in terms of geography and strategy; it also significantly contributes to economies of cities and countries in which they are located. In this thesis, the latest stage reached in the works performed in Istanbul Financial Center (İFM) project starting as one of the most important projects in Turkey in 2009 has been assessed and compliance with national and international norms such as action plans, European Union (EU), General Agreement on Tariffs and Trade (GATTs) has been questioned. To what extent the stock indices of developed countries in the world are co-integrated between October, 2005- the date in which EU negotiations began- and December 2015 has been tested econometrically. It has been concluded that stock index of ISTANBUL STOCK EXCHANGE (BİST) is not cointegrated with stock exchanges of US, HONG KONG, DUBAI, EUROSTOXX50, ENGLAND and SWITZERLAND in the above-mentioned period. The said empirical finding means that there is not long-term connection between variables. Although Istanbul has significantly proceeded in the ranking of developed financial centers considering the work done towards becoming a FC it has been observed that it has not reached the desired level yet. Istanbul Financial Center, General Agreement on Tariffs and Trade (GATTs), Turkey - EU Relations, European Union, International Financial Centers, Cointegration Analysis
Keywords: Avrupa Birliği; Dış ekonomik ilişkiler; Türkiye